VD_FINDINFO HC / 2015 / 174 vom 18. Februar 2015 - VD Tribunal cantonal (2015)
AUTORITÉ DE CONCILIATION, COMPARUTION PERSONNELLE, REPRÉSENTATION EN PROCÉDURE, SIGNATURE, FORMALISME EXCESSIF | 130 al. 1 CPC (CH), 132 al. 1 CPC (CH), 149 CPC (CH)